1999
DOI: 10.1029/98ja02681
|View full text |Cite
|
Sign up to set email alerts
|

Solar minimum streamer densities and temperatures using Whole Sun Month coordinated data sets

Abstract: Abstract.We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
171
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(195 citation statements)
references
References 26 publications
21
171
3
Order By: Relevance
“…It is worth noting that the quiescent streamer reported by Uzzo et al (2006) was at a similar latitude to the one investigated here and was observed in April 2003 while the solar activity was still decreasing. Conversely, the equatorial streamers of Gibson et al (1999) and Strachan et al (2002), the equatorial and mid-latitude active region streamers of Parenti et al (2000) and the depleted-core equatorial streamer of Frazin et al (2003) were observed during a minimum phase of the solar activity. The results presented by Ventura et al (2005) concern a collection of streamer observations performed at different latitudes in 1997 and 2000, hence near solar minimum and maximum respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the quiescent streamer reported by Uzzo et al (2006) was at a similar latitude to the one investigated here and was observed in April 2003 while the solar activity was still decreasing. Conversely, the equatorial streamers of Gibson et al (1999) and Strachan et al (2002), the equatorial and mid-latitude active region streamers of Parenti et al (2000) and the depleted-core equatorial streamer of Frazin et al (2003) were observed during a minimum phase of the solar activity. The results presented by Ventura et al (2005) concern a collection of streamer observations performed at different latitudes in 1997 and 2000, hence near solar minimum and maximum respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This can reasonably apply to our case, because the wind velocity may be considered as a minor term in force balance. Actually, the radial outflow velocities determined in this study reach values of about 100 km s −1 at heights around 5 R , while the thermal velocities of electrons corresponding to the temperatures found in the examined streamer are significantly higher than this value everywhere (see also the discussion in Gibson et al 1999). The computations were carried out using both the density profile deduced from LASCO C2 pB data inversion and the one giving the best fit of the O vi observations.…”
Section: Diagnostics Of Physical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the real coronal density distribution we make use of two different density radial profiles n e,cor available in the literature, representing two different extremes of electron density values. In particular, we set as input for our calculations either the coronal hole density distribution modeled by Cranmer et al (1999) or the streamer density profile at solar minimum derived by Gibson et al (1999), respectively given by …”
Section: Estimate Of Blob Electron Densitymentioning
confidence: 99%
“…Cranmer et al, 1999; Antonucci et al, 2000). The coronal electron temperature, T e , assumed in the analysis, is that derived by Gibson et al (1999) for the minimum of solar activity and varies between 1.5×10 6 K and 9.5×10 5 K in the range of distance 1.5-2.5 R ⊙ . We point out that the T e values do not influence significantly the results of the analysis of electron density and outflow velocity: by assuming the electron temperature values of coronal hole, the obtained results are within the errors shown in Figures 7 and 8 (see the following section).…”
Section: Discussionmentioning
confidence: 99%